Reconstruction of Branding and Promotion Strategies to En-hance the Attractiveness of New Student Enrollment at Pri-vate Polytechnics in the City of Medan - Ratih Amelia; Satria Tirtayasa; Zakia Fadila; Ahmad Fadli; Yochi Elanda (Yayasan Bina Bisnis Nusantara Medan, 2026)
This study aims to analyze the influence of promotion, accreditation, and brand image on student attractiveness in private polytechnics in Medan City. The background of this study is driven by the declining number of student enrollments, which is associated with less effective promotional strategies, suboptimal accreditation quality, and weak institutional branding. This research employs a quantitative approach with an associative method. Data were collected through questionnaires using a Likert scale, supported by documentation and literature review. The data were analyzed using validity and reliability tests, descriptive analysis, classical assumption tests, and multiple linear regression analysis, followed by hypothesis testing through t-test and F-test. The results indicate that promotion, accreditation, and brand image partially have a positive and significant effect on student attractiveness. Simultaneously, these three variables also show a significant influence on student attractiveness. Among the variables, brand image is identified as the most dominant factor affecting student attractiveness. These findings suggest that increasing student enrollment cannot rely on a single factor, but requires an integrated approach involving effective promotional strategies, improvement of institutional quality through accreditation, and strengthening of institutional brand image. This study contributes to the development of marketing strategies in higher education institutions and provides practical insights for improving institutional competitiveness in an increasingly competitive educational environment